The influence of environment on the star formation properties of galaxies - Rodríguez Del Pino, Bruno (2015)
This thesis explores the properties of galaxies that reside in regions of high density and the influence of the environment in their evolution. In particular, it aims to shed more light on the understanding of how galaxies stop forming stars, becoming passive objects, and the role played by environment in this process. The work presented here includes the study of the properties of galaxies in clusters at two different stages of their evolution: we first look at cluster galaxies that have recently stopped forming stars, and then we investigate the influence of environment on galaxies while they are still forming stars.